AN ERROR ANALYSIS ON COMPARISON AND CONTRAST PARAGRAPH WRITING OF THE SECOND SEMESTER STUDENTS’ OF ENGLISH EDUCATIONAL DEPARTMENT AT PGRI UNIVERSITY OF BANYUWANGI - Reta Septariya Eki Ayu Nadya; Nur Hasibin; Tri Mulyati (LUNAR, 2024)
This research is error analysis research on students’ comparison and contrast paragraph writing of the second semester students’ of English Educational Department at PGRI University of Banyuwangi. The aims of this research was to identify the types of errors in writing comparison and contrast paragraph made by second semester students’ at PGRI University of Banyuwangi. Using a purposive sample, students in the second-semester of the 2021/2022 academic year were selected as samples in this study. The research study is classified into a descriptive qualitative study. The data source were collected from the students’ writing of second semester. The instrument used in this research is the document. Corder theory becomes the main key in the data analysis. Based on the analysis of the grammatical errors, four types of errors were found. These four errors are as follows. In class A, there are 18 total error sentences with 4 types of errors (six errors in omission, five in addition, two in misformation, and three in misordering). Meanwhile, in class B, there are 7 of total errors sentence with 4 types of errors, they are two errors in omission, two in addition, two in misformation, and one in misordering.